An Evaluation of the Mechanical Properties, Microstructures, and Strengthening Mechanisms of Pure Mg Processed by High‐Pressure Torsion at Different Temperatures. Issue 10 (17th July 2022) - Li, Zhuoliang; Ding, Hua; Huang, Yi; Langdon, Terence G.
Abstract : Pure Mg samples are processed by high‐pressure torsion (HPT) for up to ten turns at temperatures of 293 and 423 K. The microstructures of these samples are significantly refined and bimodal structures are obtained after 10 turns of HPT processing at both 293 and 423 K. Tensile experiments are conducted at room temperature to reveal the mechanical properties of pure Mg subjected to HPT processing at different temperatures. The yield strength increases with increasing numbers of turns after processing at 293 K whereas the yield strength shows almost no variation with increasing numbers of turns at 423 K. Pure Mg processed at 423 K exhibits a higher strain hardening ability and a larger uniform elongation than after processing at 293 K. Calculations show that the grain size, bimodal structure, and dislocation density are the main factors affecting both the yield strength of the material and the work hardening behavior. Abstract : Pure Mg samples were processed by ten turns of high‐pressure torsion at both 293 and 423 K. For processing at 293 K, coarse grains were gradually refined with the accumulated strain whereas for processing at 423 K grain refinement was achieved through dynamic recrystallization leading to bimodal microstructure. Both dislocation density and grain size make contributions to the strengthening mechanism.